2011
DOI: 10.1111/j.1468-0351.2011.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Democracy and prosperity in two decades of transition1

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Heckelman (2010a) shows that broad democracy indexes created by Freedom House are positively correlated with economic growth in transition economies, but the effects can differ by democracy category. Apolte (2010) also shows that an increase in the level of democracy in transition economies turns out to be growth enhancing. Further, the estimated effect is stronger the lower is the initial level of democracy.…”
Section: The Literaturementioning
confidence: 94%
“…Heckelman (2010a) shows that broad democracy indexes created by Freedom House are positively correlated with economic growth in transition economies, but the effects can differ by democracy category. Apolte (2010) also shows that an increase in the level of democracy in transition economies turns out to be growth enhancing. Further, the estimated effect is stronger the lower is the initial level of democracy.…”
Section: The Literaturementioning
confidence: 94%
“…The authors conclude that although economic freedom positively affects economic performance in transition economies, political freedom is neutral for economic growth. Apolte (2011), using data on democracy, liberalization, and income for a sample of 25 transition economies for the period 1991-2011 found that only a moderate level of democratization has a significant positive effect on economic growth, while the acceleration of democratization leads to a decrease in growth rates. The author explains this ambiguous result by the institutional features of different countries in which formal democratic structures are embedded or on which they are superimposed.…”
Section: Le Link Between Democracy and Economic Growth In Transition ...mentioning
confidence: 99%
“…Despite a large body of theoretical and empirical literature examining the issue, no scientific consensus has been reached. In addition, it has not been achieved in studies concerning transition countries [2][3][4][5][6][7]. Researchers who use different approaches and methods in assessing this phenomenon sometimes come to opposite conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…The results of more recent-and econometrically more sophisticated studies-are less diverse, but still not unambiguous. Acemoglu et al (2019), Flachaire et al (2014), Gründler and Krieger (2016), Tabellini (2008, 2009), Knutsen (2015), Madsen et al (2015), and Papaioannou and Siourounis (2008) find that democracy positively affects economic growth, whereas Apolte (2011), Aisen and Veiga (2013), and Murtin and Wacziarg (2014) find that political regimes do not affect economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%